Employing DC resistivity method for hydrogeological analysis of Zuma II, a VES approach (2017)
This research work employs the DC Resistivity method for Hydrogeological analysis in Veritas University, Zuma II, Bwari Area Council, Abuja, FCT, Nigeria. The work attempts to tackle the immense water shortage crisis within the University, this work also, attempts to provide access to stratigraphic information and to assist groundwater development for the region. Schlumberger array and electrical sounding technique are adopted for subsurface delineation. Eleven resistivity profile graphs generated from tabled data are presented by employing the Winresist software and Microsoft excel. A The outcome of this investigation revealed four spots with good potentials for ground water; these points are located within the fifth and third layers on 9.28498°N, 7.41875°E (VES 1); 9.28515°N, 7.41789°E (VES 5); 9.28437°N, 7.41793°E (VES 8); 9.28394°N, 7.41792°E (VES10). Furthermore, the outcome of this work revealed the lithology of the region investigated. Five distinct layers of varying thicknesses and depths were displayed: Top soil, Clay, Sandy clay, Fractured and Basement Rocks. From the collated readings, the derived average thicknesses of topsoil, sandy clay and clay are 0.8 m, 10.2 m and 7.06 m respectively.